Stating the need for an architectural design process: The role of the space syntax method in a case study of Western Australia project homes - Perugia, Francesca (2015)
Within the existing literature, the Space Syntax approach to the reading and understanding of the built environment has been strongly connected to evaluations of the efficacy of the result of design processes. If we define design as the process of recognising, analysing and expressing possible connections between identified problems and potential tangible solutions, the evaluation of the final product, the building, assumes as much relevance as the definition of the problem itself. This paper aims to explore the opportunities offered by the use of the Space Syntax investigative approach, in order to both justify the need for a design process to be initiated, and to facilitate the design process itself, by identifying design-related problems. The research focuses on the design of the most successful, affordable housing model currently on the market in Australia, the 'project home'. By describing the implicit structure of the space configuration of the available assortment of project home designs, the Space Syntax methodological approach uncovers their limited typological categories, three identified genotypes. The analysis of housing designs, using Space Syntax approach, clearly shows the detachment of the analysed housing designs from the housing needs of the society that they should be meeting, highlighting and justifying the need for an alternative design process to be initiated. Moreover, by describing and classifying current housing designs, the Space Syntax analysis provides an opportunity to reflect on how to use its findings to inform and approach future design proposals.